THE AMOUNT OF ALKALOIDS CONTAINED IN THE VEGETATIVE AND GENERATIVE ORGANS OF THE DATURA INNOXIA MILL PLANT - Po‘latov Sarvar Mustafoyevich; Xashimova Madinabonu Raxmonberdi qizi (Web of Journals Publishing, 2024)
Due to the increasing demand for natural medicines in the world medicine, the introduction and development of agro-technologies for the cultivation of wild medicinal plants in irrigated farming areas, which are carried out to increase the yield and improve the quality of the products obtained from them special attention is paid to research. It is especially important to carry out research on the correct definition of feeding with mineral fertilizers, especially nitrogen fertilizers, and the development of feeding standards in the cultivation of the Datura innoxia Mill plant.
Keywords: Medicinal, datura, herbal, vegetative, generative, alkaloids, cultivation.